Pengaruh Kualitas Pelayanan Tenaga Kesehatan Terhadap Kepuasan Masyarakat di UPTD Puskesmas Paguyaman Pantai Kabupaten Boalemo - Taib, Siskawati; Arifin Tahir; Rustam Tohopi (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2025)
This study aims to determine the effect of health service quality on community satisfaction at the Paguyaman Pantai Health Center UPTD, Boalemo Regency. The sample in this study amounted to 248 respondents. The type of data used in this study is primary data. Data collection was carried out through the distribution of questionnaires. The method used for data analysis is basic linear regression. With a determination coefficient of 68.50%, the results of this study indicate that community satisfaction at the Paguyaman Pantai Public Health UPTD is positively and significantly influenced by the quality of health service providers. Meanwhile, the remaining 31.00% is influenced by other variables not examined in this study, such as service accessibility, facilities and infrastructure, communication and information, drug availability, and additional services. The positive test results imply that the higher the level of public satisfaction with the Paguyaman Pantai Public Health UPTD, the higher the public satisfaction with the Paguyaman Pantai Public Health UPTD. The increase in public satisfaction at the Paguyaman Pantai Health Center UPTD occurred due to an increase in the quality of services provided by health workers.